Learning to Teach through Recursive Boundary Crossing in the Teaching Practicum. (17th November 2022) - Wang, Zhaoxuan; Yuan, Rui; Liao, Wei
ABSTRACT: Informed by a conceptual framework on boundary crossing, this qualitative case study explored how a student teacher engaged in professional learning through recursive boundary crossing between her field school and the university programme in a U.S. context. The findings revealed the power of boundary crossing as a cyclical, intense, and transformative learning mechanism that helped the student teacher connect teaching knowledge and experiences acquired at different sites and facilitated her reflective practice and self-transformation. However, the lack of communication between the university and the field school caused a cognitive disturbance and emotional challenges for the student teacher. The study concludes with practical implications for reforming teaching practicum to maximise the potential of boundary crossing for teacher learning.